(untitled) (Dhaka University Journal of Biological Sciences, 2012)
A male-removal experiment was performed to determine if the value of male parental care depended on the timing of the help. In the experiment male parent was removed before the carcass was prepared for breeding, after partial carcass preparation, after complete carcass preparation, before direct care for the larvae and males were allowed to disperse naturally after caring for the larvae. It was found that where the male provided complete pre-hatching care or both preand post-hatching care offspring were larger and in better condition. Mass of offspring at eclosion was affected by male removal (F3,1266 = 5.087, p = 0.002) though size of offspring was not affected by the treatment group. Complete prehatching care had a positive effect on development compared to limited care (F3, 1267 = 8.501, p < 0.000) but this effect disappeared if males remained after the larvae hatched. Larval survivorship did not vary among treatments (F3,122 = 0.531, p = 0.662).